DOI: 10.33915/etd.1997
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of position and mobility of the first ray in experienced and inexperienced examiners

Abstract: Reliability of Position and Mobility of the First Ray in Experienced and Inexperienced Examiners. Crystal Shirk, BS, ATC Context: The first ray is an essential part of the gait cycle and manual measurements of the first ray are a common part of a biomechanical examination. Problems with first ray position or mobility may lead to stress fractures, hallux valgus, metatarsalgia, acquired flatfoot, tendonitis, and plantar ulcerations. Although this measurement is quite common, little research has been completed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…11,16 In normal healthy adults, the mean dorsal motion of the first ray of the foot in the sagittal plane in a nonweightloading condition is reported to be 6 mm with a range of 3 to 9 mm. 9,10,12,19 For individuals with hallux valgus, the mean value is 7 mm, which has been obtained from a wide variety of methods. 12,19 Using the EMC device, we found that patients with hallux valgus have a mean mobility of 8.3 mm, which was higher than the reported mean value of 7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…11,16 In normal healthy adults, the mean dorsal motion of the first ray of the foot in the sagittal plane in a nonweightloading condition is reported to be 6 mm with a range of 3 to 9 mm. 9,10,12,19 For individuals with hallux valgus, the mean value is 7 mm, which has been obtained from a wide variety of methods. 12,19 Using the EMC device, we found that patients with hallux valgus have a mean mobility of 8.3 mm, which was higher than the reported mean value of 7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsiflexed. If the first metatarsal head was found below the remaining metatarsals, it was graded as plantar flexed (11)(12)(13) .…”
Section: Methodsmentioning
confidence: 99%
“…6,15,16 I believe that instability exists in a small number of patients but can only be determined by stressing the joint intraoperatively. 8,11-13 5.…”
Section: Erosion Of Cristamentioning
confidence: 99%